HMGB-1 as a predictor of major bleeding requiring activation of a massive transfusion protocol in severe trauma - Frelich, Michal; Bebej, Marek; Pavlíček, Jan; Burša, Filip; Vodička, Vojtěch; Švagera, Zdeněk; Kondé, Adéla; Jor, Ondřej; Bílená, Markéta; Romanová, Tereza; Sklienka, Peter (Scientific reports, 2025)
Massive bleeding causes approximately 50% of deaths in patients with major trauma. Most patients die within 6 h of injury, which is preventable in at least 10% of cases. For these patients, early activation of the massive transfusion protocol (MTP) is a critical survival factor. With severe trauma, high-mobility group box 1 (HMGB-1, i.e., amphoterin) is released into the blood, and its levels correlate with the development of a systemic inflammatory response, traumatic coagulopathy, and fibrinolysis. Previous work has shown that higher levels of HMGB-1 are associated with a higher use of red blood cell transfusions. We conducted a retrospective analysis of previous prospective single-center study to assess the value of admission HMGB-1 levels in predicting activation of MTP in the emergency department. From July 11, 2019, to April 23, 2022, a total of 104 consecutive adult patients with severe trauma (injury severity score > 16) were enrolled. A blood sample was taken at admission, and HMGB-1 was measured. MTP activation in the emergency department was recorded in the study documentation. The total amount of blood products and fibrinogen administered to patients within 6 h of admission was monitored. Among those patients with massive bleeding requiring MTP activation, we found significantly higher levels of HMGB-1 compared to patients without MTP activation (median [interquartile range]: 84.3 μg/L [34.2-145.9] vs. 21.1 μg/L [15.7-30.4]; p < 0.001). HMGB-1 level showed good performance in predicting MTP activation, with an area under the receiver operating characteristic curve of 0.84 (95% CI 0.75-0.93) and a cut-off value of 30.55 μg/L. HMGB-1 levels correlated significantly with the number of red blood cell units (rs [95% CI] 0.46 [0.28-0.61]; p < 0.001), units of fresh frozen plasma (rs 0.46 [0.27-0.61]; p < 0.001), platelets (rs 0.48 [0.30-0.62]; p < 0.001), and fibrinogen (rs 0.48 [0.32-0.62]; p < 0.001) administered in the first 6 h after hospital admission. Admission HMGB-1 levels reliably predict severe bleeding requiring MTP activation in the emergency department and correlate with the amount of blood products and fibrinogen administered during the first 6 h of hemorrhagic shock resuscitation.Trial registration: NCT03986736. Registration date: June 4, 2019.
Keywords: dospělí; Female; skóre závažnosti úrazu; urgentní služby nemocnice; biologické markery; Blood Transfusion; Biomarkers; Adult; krevní transfuze; ženské pohlaví; Injury Severity Score; krvácení; lidé; Wounds and Injuries; protein HMGB1; retrospektivní studie; Emergency Service, Hospital; prospektivní studie; Male; Prospective Studies; Aged; Hemorrhage; lidé středního věku; rány a poranění; HMGB1 Protein; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Humans